Superallowed Nuclear Beta Decays and Precision Tests of the Standard Model - Gorchtein, Mikhail; Seng, Chien-Yeah (Annual Review of Nuclear and Particle Science, 2024)
For many decades, the main source of information on the top-left corner element of the Cabibbo–Kobayashi–Maskawa quark mixing matrix, <span class=